Analisis Penerapan JSA (Job Safety Analysis), JHA (Job Hazard Analysis) dan SOP (Standard Operasional Procedure) Sebagai Perangkat Keselamatan dan Kesehatan Kerja pada Kegiatan Produksi Pabrik Di PT. Sumbar Calcium Pratama, Kecamatan Lareh Sago Halaban, Kabupaten Lima Puluh Kota. - Yudith Ananda Pradipta; Fadhilah S.Pd, M.Si (Departemen Teknik Pertambangan FT UNP, 2022)
Abstract. At PT. Sumbar Calcium Pratama, several violations of the existing JSA ( Job Safety Analysis) , JHA ( Job Hazard Analysis) and SOP (Standard Operational Procedure) were found. There are still many workers who work in dangerous work positions, use unsafe tools, and there are still many workers who work without using personal protective equipment or PPE that has been provided by the company. The purpose of this study was to obtain an overview of the level of knowledge, attitudes, and actions on occupational safety and health by workers in the application of JSA (Job Safety Analysis), JHA (Job Hazard Analysis) and SOP (Standard Operating Procedures) as occupational safety and health tools at PT. Sumbar Calcium Pratama, Analyzing the application of JSA (Job Safety Analysis) and JHA (Job Hazard Analysis) at PT. West Sumatra Calcium Pratama, Analyzing the application of SOP (Standard Operating Procedure) at PT. West Sumatra Calcium Primary. In this study, theory is combined with field data, so that the results obtained will be analyzed to further produce a recommendation. Based on the results of the research conducted, it can be concluded the following things, first at PT. Sumbar Calcium Pratama has implemented JSA (Job Safety Analysis), JHA (Job Hazard Analysis) and SOP (Standard Operational Procedure) but has not been maximized, the results of the questionnaire regarding the application of JSA (Job Safety Analysis), JHA (Job Hazard Analysis) and SOP (Standard Operational Procedure) , the results of the knowledge purification production activity questionnaire are 82.22% with a very good value range, the results from the questionnaire purification production activities attitude is 80.83% with a good score range, the results of the action section of the purification production activity questionnaire are 83.05% with a very good value range, the results of the knowledge factory production activity questionnaire are 83.34% with a very good value range, the results From the attitude section of the factory production activity questionnaire, it was 84.15% with a very good score range, and the results of the action factory production activity questionnaire were 87.09% with a very good score range.